Problematika Sertipikat Hak Atas Tanah Yang Hilang Dalam Proses Jual Beli Tanah - Namira Muna Salsabila; Dinda Keumala (Faculty of Law, Universitas Trisakti, 2023)
The sale and purchase of land transaction can only be registered if made in front of a PPAT because the essential registration is based on the AJB made by the PPAT. The problem formulation focuses on the lost process of buying and selling land, which relies on the certification of land rights owned by the seller and how PPAT solving the obstacles and solutions. The research method is descriptive normative with secondary data and primary data in the form of interviews. The data was analyzed in a qualitative way and with deductive conclusions. The results show that the PPAT processes the production or issuance of a replacement certificate and transfers the name of the replacement certificate or registration of rights due to sale and purchase at the Land Office. However, obstacles encountered include the buyer's inability to produce the lost land certificate, the seller's whereabouts needing to be discovered, not knowing the certificate number, and the lengthy process of issuing a replacement certificate. The solution involves the PPAT requesting the Land Office to re-measure the land parcel, advising the buyer to file a lawsuit with the District Court, and directing the buyer to transfer the certificate's name immediately